Kreativitas Mahasiswa dalam Mengolah Produk Tradisional: Tempe Crunchy dan Dimsum Tahu sebagai Peluang Bisnis Kekinian - Mila Agustin; Nadya Mahamida; Karyadi Hidayat (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
Student creativity in the world of entrepreneurship is a crucial factor in creating competitive product innovations in the modern era. This study illustrates how students are able to transform traditional products into high-value innovations through the development of Tempe Crunchy and Dimsum Tofu. Processing traditional products with innovative touches, such as flavor variations, modern packaging, and digital marketing strategies, has been proven to increase consumer interest and open up new business opportunities among the younger generation. Tempe Crunchy presents distinctive Indonesian flavors in a convenient, light snack, while Dimsum Tofu combines local culinary elements with contemporary food trends. Students' creativity in modifying traditional products demonstrates the important role of the younger generation in preserving the archipelago's culinary heritage while developing a competitive creative economy in the modern era.